Efficient Genome Editing by a Miniature CRISPR-AsCas12f1 Nuclease in Bacillus anthracis - Wang, Yanchun; Sang, Shuli; Zhang, Xin; Tao, Haoxia; Guan, Qing; Liu, Chunjie (Frontiers in Bioengineering and Biotechnology, 2022)
A miniature CRISPR-Cas12f has been demonstrated to serve as an effective genome editing tool in gram negative bacteria as well as human cells. Here, we developed an alternative method to edit the genome of Bacillus anthracis based on the AsCas12f1 nuclease from Acidibacillus sulfuroxidans. When the htrA gene on the chromosome and the lef gene on the plasmid pXO1 were selected as targets, the CRISPR-AsCas12f1 system showed very high efficiency (100%). Our results also indicated that the length of the homologous arms of the donor DNA had a close relationship with the editing efficiency. Furthermore, a two plasmid CRISPR-AsCas12f1 system was also constructed and combined with the endonuclease I-SceI for potential multi-gene modification. This represents a novel tool for mutant strain construction and gene function analyses in B. anthracis and other Bacillus cereus group bacteria.